Estudo teórico da seletividade e do solvente em um nanobiossensor de herbicidas inibidores da acetil-coenzima a carboxilase - Mendes, Carla Cristina Alves (2014)
The nanobiosensors are devices of detection that have as recognition elements a biological material. This work is a proposal of the nanobiossensor to detect specific inhibitor herbicides acetyl co-enzyme A carboxylase (ACC), whose has effectively proved in detecting herbicide diclofop compared with the presence of atrazine in the sample to being analyzed. This nanobiossensor consists of an atomic force microscopy (AFM) that has its tip functionalized with the enzyme ACC; and the detection is performed by measures the force between the AFM tip and the sample studied, which is originated in interaction strength of the enzyme-herbicide. Due to these interactions, which occur between enzyme and substrate, the advantage of the nanobiosensor is its selectivity and sensitivity for detecting concentrations that would not be accounted for in conventional methods of sensors and biosensors. Given the use of nanobiosensor with functionalized AFM tip, this study aimed to verify the selectivity of it for two specific classes of herbicides that are inhibitors of ACCase: the aryloxyphenoxypropionates (fops) and cyclohexanediones (dims). For this, molecular docking calculations with 12 herbicides were made, and this methodology evaluated the best conformation of the complex enzyme-substrate and free energy of interaction. This study also proposed to verify the effect that the presence of water causes on the selectivity and sensitivity of detection, making necessary the use of Molecular Dynamics simulation of the ACC with subsequent docking calculations. The results show that the best interaction energies of the complexes were formed with the fops and dims herbicides, however two other herbicides, imazaquin and metsulfuron, showed a comparable binding energy of specific inhibitors, primarily due to the similarity in the type intermolecular interactions thought hydrogen bonding interactions with the ILE-1735 and ALA-1627, so these herbicides may interfere in detection for the nanobiosensor. The presence of water molecules increases the bind energy, making them more unfavorable for the specific inhibitors herbicides, which can slightly affect the sensitivity of detection. In general, the selectivity was not affected because the fops and dims continued with more favorable energy values when compared with other herbicides.